The Case for Harmonizing Fault in Private Enforcement of EU Competition Law - Balčiūnas, Tomas; Sluijs, Jasper P. (Thomson Reuters, 2021)
In this article we explore fault as it has traveled from public enforcement to private enforcement of EU competition law and beyond the implementation of the Damages Directive. We demonstrate how differences between national tort law systems have prevented harmonization of fault in the Damages Directive. This leads us to point out the current different fault standards across Member States in private enforcement of competition law, ranging from strict liability, to a rebuttable fault presumption to a fault requirement. This variety of fault standards induces forum shopping between Member States, and has a negative effect on the European Internal Market’s level playing field. Given these adverse effects, we argue for harmonization of a fault standard in private enforcement of competition law, and find that harmonizing towards a rebuttable presumption of fault both is best in line with fair trial provisions, and best observes the effectiveness of EU competition law.
Keywords: competition law; Private enforcement; Damages Directive; Fault; antitrust Damages Directve; Antitrust law; Taverne